Membangun Kesadaran Anti-Plagiarisme : Pelatihan Etika Penulisan Ilmiah di Pondok Pesantren Miftahul Khaer - Dwi Septiani; Siti Yuniarsih; Hesti Diana; Putri Okta Sanggari; Risma Nurullita; Juniadi Gulo (Lembaga Pengembangan Kinerja Dosen, 2025)
Plagiarism remains a critical challenge in academia, including in religious-based educational institutions like Islamic boarding schools (pondok pesantren). This Community Service Program (PKM) aimed to enhance students' awareness and skills in avoiding plagiarism through scientific writing ethics training at Miftahul Khaer Islamic Boarding School. The method employed capacity building via interactive workshops covering plagiarism definitions, types, impacts, citation techniques (APA Style), paraphrasing, and plagiarism detection tools (e.g., Turnitin). Post-training evaluations revealed significant improvements: participants’ understanding of plagiarism rose from 14.3% to 74.3%, with average comprehension scores increasing from 2.97 to 4.76. Knowledge of plagiarism types achieved an average score of 4.51, though technical proficiency with detection tools remained lower (score: 3.14). Despite internet connectivity limitations, printed learning materials ensured training effectiveness. The initiative successfully fostered an ethical academic culture, with recommendations for sustained programs integrating practical case studies, digital tools, and curriculum integration to strengthen academic integrity in the pesantren environment.